Ibn Khaldun's Storytelling History and Contribution of Thought to the World of Education - Ahmad Roni Maulana Setiawadi; Encung Encung (al-Wadhih: Journal of Islamic History and Civilization, 2025)
This article examines Ibn Khaldun’s educational thought through an exploration of his biography, intellectual background, and the theoretical framework underlying his ideas on educational objectives, curriculum, and teaching methods. The study reveals that Ibn Khaldun’s life journey divided into four significant periods had a profound influence on the development of his intellectual outlook, particularly during his period of isolation (‘uzlah), which resulted in the composition of Muqaddimah, a foundational work in social and educational thought. According to Ibn Khaldun, education has multidimensional aims: developing intellectual capacity, enhancing social quality, and perfecting spirituality. The curriculum he formulated encompasses linguistic sciences, transmitted (naqlī) sciences, and rational (‘aqlī) sciences, all arranged proportionally and adaptively in response to social change. Meanwhile, his proposed teaching methodology emphasizes a gradual learning process, avoidance of indoctrination, and rejection of any form of coercion in education. This study concludes that Ibn Khaldun’s educational thought is comprehensive, systematic, and highly relevant to the development of modern Islamic education, as it emphasizes habituation, guidance, and holistic personality formation.